The Influence of Incentive Policies and Work Motivation on Employee Loyalty at the Arista Hotel Palembang - Bella Nabillah; Hamid Halin; Shafiera Lazuarni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine the effect of incentive policies and work motivation on employee loyalty at The Arista Hotel Palembang In this study, respondents' data collection filled out a questionnaire with a Likert scale. The population in this study were employees of The Arista Hotel in the Southern Sumatra Region totaling 84 non-permanent employees. Incentive policy (X1) in the test results on employee loyalty (Y) obtained a tcount value of 0.15 smaller than the t table value of 1.989 and a significance value of -0.874 greater than the alpha value of 5% or 0.05, so the conclusion is that the effect of incentive policy (X1) has no significant effect on employee loyalty (Y). Motivation (X2) in the test results on employee performance (Y) it is known that the t value of 6.795 is greater than the t table value of 1.989 and the significance value of 0.000 is less than the alpha value of 5% or 0.05 so the conclusion is that work motivation (X2) has a significant effect on employee loyalty (Y). While the F test shows that all models tested on the variables have a significant effect on the dependent variable with a value at sig less than 0.05, so all independent factors affect the dependent variable. As well as simultaneously, that 62.4% of employee loyalty indicators are influenced by incentives and work motivation only, while 37.6% is influenced by factors not taken into account in this study.